Faktor - Faktor yang Mempengaruhi Pemilihan Kontrasepsi Non MKJP pada PUS - Jenie Palupi; Syiska Atik Maryanti; Ida Prijatni; Aisyah Zahroh Wahidiyah (Puslitbang Sinergis Asa Professional, 2023)
The family planning program is the most basic preventive health effort for women. Based on data from the East Java Provincial Health Office in 2017, 77.1% of new family planning acceptors and active family planning acceptors used non-MJKP contraception, while 23% used MJKP contraception.The high number of non-MKJP contraceptive acceptors is caused by several factors including age, education level, number of children, husband's support. This study aims to determine the factors that influence the selection of Non-MKJP contraception in the Tapen Puskesmas District of Bondowoso. This study is a comparative study with a cross sectional approach, using Simple Random Sampling with a sample consisting of 110 Non MKJP contraceptive acceptors. The instrument used was a questionnaire. Data were analyzed using chi-square. The results obtained 69.1% of mothers with a healthy reproductive age category, mothers at the Senior High School (SMA) education level of 55.5%, mothers who had 2 children were 51.8%, and those who received husband's support were 80.0 %. Data were analyzed by chi-square test. The results of the bivariate analysis showed that the age factor showed (p = 0,000), education level (p = 0,000), number of children (p = 0,000), husband's support (p = 0,000). The α value of the four factors is 0.05. Age, education level, number of children, husband's support are influenced by the high number of non-MKJP contraceptive acceptors in the work area of ​​Tapen Puskesmas, Bondowoso Regency. Government efforts have been good in suppressing birth rates by providing information about Non-MKJP contraception and making the Non-MKJP contraceptive method as one of the methods that is quite effective and able to help the success of government programs especially in the field of KB Keywords: Contraception acceptors, MKJP, Fertile Age Couples (PUS)